KONSEP TRANSITIONAL JUSTICE DALAM PENANGANAN PELANGGARAN HAM BERAT DI INDONESIA - Asher Tumbo (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2020)
Authoritarian state power always has an impact on violations of human rights. In fact, in a period of authoritarian change of power in a country towards democratic governance often leaves scars in the form of gross violations of human rights. This condition is exacerbated by the inability of the judiciary to provide a sense of justice for victims of gross human rights violations committed by the ruling government. Indonesia has also experienced the same thing, where gross violations of human rights were committed by an authoritarian government. Some of the gross violations of human rights have not even been resolved to date. The concept of Transitional Justice is considered to be one of the answers to the problem of gross human rights violations that have occurred in Indonesia.This article will analyze the concept of Transitional Justice in dealing with gross human rights violations in Indonesia.The purpose of this paper is to find out the application of the concept of Transitional Justice in Indonesia.Based on the analysis used, it was found that the application of the concept of Transitional Justice in Indonesia could be done if there was an institution called the Truth and Reconciliation Commission.